Uji Variasi Tekanan Nozzel Terhadap Emisi Gas Buang Ramah Lingkungan Mesin Disel Type DL 41 - GINTING, TINUS (Journal of Engineering and Information Technology for Community Service, 2024)
This study aims to examine the exhaust emissions of HC (ppm) and CO (%), through variations in nozzle pressure and rotation variations. research samples using engine stand 2765 CC, diesel fuel. through variations in rotation 1500 rpm, 2500 rpm, 3500 rpm and nozzle pressure 160 kg/cm2, 180 kg/cm2, and 190 kg/cm2 measured exhaust emissions on the engine smoke tester. The results concluded that the variation of nozzle pressure and rotation has an effect on exhaust emissions, the lowest HC (ppm) exhaust emission value at 160 kg/cm2 nozzle pressure at 1500 rpm, while the lowest CO (%) exhaust emission value occurred at 180 kg/cm2 nozzle pressure at 3500 rpm.